Analisis Produktivitas Tower Crane pada Pembangunan Gedung Gereja Kemah Tabernakel Pantai Indah Kapuk 2 - Haholongan M, Aris Pistar; Putra, I Nyoman Dita Pahang (Dinasti Research, 2025)
The implementation of project work often encounters obstacles, with delays in time being the most common issue. The use of heavy equipment is one of the factors that helps accelerate the project execution to align with the project plan. This study aims to compare the productivity of tower crane on site with the produtivity based on specification. In this research, two types of tower cranes were used, namely the Potain MC 465 and the Potain MC 310 K12. The study was conducted over 20 days, observing the volume of materials transported and the cycle time required to lift the materials. The results of the study show that the average productivity of the Potain MC 465 tower crane on-site is 11,135.492 kg/hour, while the specification indicates 12,286.752 kg/hour. For the Potain MC 310 K12 tower crane, the on-site productivity is recorded at 8,506.263 kg/hour, and 9,197.890 kg/hour according to the specifications. The difference in productivity between the actual site conditions and specifications reflects a decrease in equipment performance, with a percentage reduction of 9.37% for Potain MC 465 and 7.519% for Potain MC 310 K12. This decrease in productivity is caused by the difference in cycle time observed on-site compared to the time specified in the equipment specifications. The average cycle time for Potain MC 465 on-site is 3.256 hours, while the specification indicates 2.961 hours. For Potain MC 310 K12, the cycle time on-site is 3.948 hours, while the specification is 3.658 hours. The difference in cycle time between actual site conditions and specifications shows a reduction of 9.96% for Potain MC 465 and 7.93% for Potain MC 310 K12.